257 POSITIVE HEALTH AND AGING FOR OLDER IRISH TRAVELLERS AND OLDER PEOPLE WHO HAVE EXPERIENCED HOMELESSNESS: LIFE-COURSE MEANINGS AND DETERMINANTS. (18th November 2021) - Walsh, K; Carroll, C; Scharf, T; O'Donovan, D
Abstract: Background: The position of marginalized groups of older people remains neglected in positive health and aging (PHA) agendas, whether they concern healthy, active or positive aging. Questions exist around the meaning of such constructs, and the factors that enable disadvantaged populations to achieve equitable later-life experiences. In focusing on two such groups, this study investigates the constituent dimensions of PHA for older Irish Travellers and older people who have experienced homelessness, and the role of life-course and structural determinants in constructing PHA trajectories for these groups. Methods: The study involves a multi-method qualitative, participatory voice-led methodology, but the analysis draws primarily on 49 in-depth life-course interviews with the populations. Results: In addition to five interconnected dimensions of PHA, four determinants related to life-course experiences and structural factors are identified: social relations; material and accommodation circumstances; formal supports and systems; and critical transitions and resilience. Conclusion: While illustrating the validity of PHA agendas for these groups when understood through their lived experiences, the findings highlight the significant deprivations and risks to rights that must be accounted for to secure meaningful gains in PHA for the groups.